The International Wine Trade and Its New Export Dynamics (1988–2012): A Gravity Model Approach. Issue 4 (1st March 2016) - Castillo, J. Sebastián; Villanueva, Emiliano C.; García‐Cortijo, M. Carmen
ABSTRACT: An acceleration of the wine industry globalization process has occurred in the last decades due to increased competition, the emergence of new producers and exporters, and the existence of new wine consuming countries. All this has led to global changes in production strategies and marketing. The aim of this paper is to analyze the changes that have occurred in the global wine export dynamics and define its determinants; to do so a gravity model was estimated in which (a) the main wine producers and consumers involved in international trade are present, (b) two distinctive scenarios are present: one of continuous change (1988–1999), and one of an established export dynamic (2002–2012), and (c) bulk and bottled wines are considered. The main results show that higher incomes, lower prices, cultural and geographical affinities, and trade agreements promote wine exports; the expansion of bottled wine trade, especially within the EU, is particularly highlighted. [EconLit citations: C40; F14; Q1].